Soil nutrient cycling and performance of Pea crop under natural farming practice - Patra, Nibedita; Thakuria, Dwipendra (Umiam : CPGSAS, CAU(Imphal), 2024)
Soil nutrient cycling involves a complex interplay of biochemical, chemical, and physical processes. This cycle is primarily driven by the metabolic activities of diverse soil microorganisms, including bacteria, fungi, and archaea, as well as the interactions between plant roots and soil fauna. These biotic factors work together with abiotic chemical and physical phenomena to regulate the transformation, availability, and cycling of essential nutrients in the soil matrix. Pea (Pisum sativum L.) is a significant rabi season crop, particularly valued for its ability to fix nitrogen through a symbiotic relationship with rhizobium bacteria in the soil. Optimizing nutrient management through traditional practices like biofertilizers and organic preparations such as Jeevamrutha and Beejamrutha could improve soil health and productivity. However, scientific research on soil nutrient cycling under natural farming, especially in the acidic soils of Northeast India, is still lacking. By considering the above research gap a pot experiment was conducted with following objectives (a) To analyze the effects of bioinputs on soil nutrient cyclingparameters (b) To determine the growth, yield and nutrient uptake of pea crop under bioinput combinations. In this experiment, two factors were tested: soil management (M) and seed treatments (S). Soil management had four treatments: M1 (Organic Manure), M2 (M1 + Crop residue mulch), M3 (M1 + Jeevamrutha), and M4 (M2 + Jeevamrutha). Seed treatments included three treatments: S1 (No seed treatment), S2 (Beejamrutha), and S3 (Biofertilizer). This created a total of 12 treatment combinations, each replicated three times, resulting in 36 pots. One subset constituting of 36 pots was used for destructive sampling to analyze physiological stress and root parameters, while the other subset was used to study plant and soil process parameters, making a total of 72 pots in the experiment. Experimental findings revealed that soil pH and soil organic carbon (SOC) was slightly influenced only by the soil management with M4 treatment (4.91 and1.58% respectively), whereas there was no significant difference in case of seed treatment. In terms of soil biochemical parameters, soil management with M4 treatment showed significantly highest MBC [418 (So(Bg g-1 (dw) soil], MBN [73.6 (So(Bg g-1 (dw) soil], MBP [11.3 (So(Bg g-1 (dw) soil], DHA [7.05 (So(Bg (TPF) g-1 (dw) soil h-1], GSA [39.6 (So(Bg (pNP) g-1 (dw) soil h-1], PHA [178 (So(Bg (pNP) g-1 (dw) soil h-1]. Among the seed treatments, S3 showed highest MBC [405 (So(Bg g-1 (dw) soil], MBN [69.2 (So(Bg g-1 (dw) soil], MBP [11.2 (So(Bg g-1 (dw) soil], DHA[6.93 (So(Bg (TPF) g-1 (dw) soil h-1], GSA [38.6 (So(Bg (pNP) g-1 (dw) soil h-1], PHA [176 (So(Bg (pNP) g-1 (dw) soil h-1]. Additionally, soil Avl-N, Avl-P, Avl-K content (364 kg ha-1, 35.4 kg ha-1, 209 kg ha-1 respectively) also significantly increased with soil management, highest being under M4 treatment. Plant growth parameters such as plant height (30, 60, 90 DAS and harvest), number of pods plant-1, number of seeds pod-1, dry shoot weight were significantly influenced by the soil management and seed treatment. Dry pod and dry seed yield also showed significantly higher values (4.41 g plant-1, 3.33 g plant-1, 4.18 g plant-1, 3.26 g plant-1 respectively in terms of both soil management with (M4) and seed treatment with (S3) respectively. The root area, root length, number of root tips, root volume and number of root nodules were statistically comparable among soil management and seed treatment. Physiological stress parameters such as Cell membrane stability and total chlorophyll content in fresh leaves increased significantly in terms of soil management (M4) and seed treatment (S3), whereas the MDA content in fresh leaves lowered in M4 and S3 treatment. The N,P, and K content in stover and seed was also found to be highest in M4 treatment (15.9 mg g-1 stover, 4.31 mg g-1 stover, 14.6 mg g-1 stover, 33.2 mg g-1 seed, 4.58 mg g-1 seed, 12.4 mg g-1 seed respectively) and S3 treatment (15.2 mg g-1 stover, 4.11 mg g-1 stover, 13.7 mg g-1 stover, 32.7 mg g-1 seed, 4.60 mg g-1 seed, 11.7 mg g-1 seed respectively). In conclusion, it can be recommended that the integration of natural farming component with biofertilizer consortium may be a potential option for higher productivity of pea crop by supporting enhanced nutrient cycling in acid soil.s
Includes bibliographical references.
Keywords: Soil -- Nutrient content; Soil -- Nutrient management; Pea -- Natural farming; Beejamrutha; Jeevamrutha